Increased Galactosidase Beta 1 Expression as a Senescent Key Factor in β-Cells Function Modulation at the Early Steps of Type 2 Diabetes - Maduro, Ana T.; Pinto, Anabela; Ferreira-Gomesb, Joana; Costa, Raquel; Soares, Raquel; Luís, Carla (Experimental and Clinical Endocrinology & Diabetes, 2023)
Background In type 2 diabetes, insulin resistance is observed, and β-cells are incapable of responding to glycemia demands, leading to hyperglycemia. Although the nature of β-cells dysfunction in this disease is not fully understood, a link between the induction of pancreatic β-cell premature senescence and its metabolic implications has been proposed. This study aimed to understand the relationship between diabetes and pancreatic senescence, particularly at the beginning of the disease.Methods C57Bl/6 J mice were fed two different diets, a normal diet and a high-fat diet, for 16 weeks. Pancreatic histomorphology analysis, insulin quantification, inflammation parameters, and senescence biomarkers for the experimental animals were assessed at weeks 12 and 16.Results The results proved that diabetes onset occurred at week 16 in the High Fat Diet group, supported by glycaemia, weight and blood lipid levels. Increased β-cells size and number accompanied by increased insulin expression were observed. Also, an inflammatory status of the diabetic group was noted by increased levels of systemic IL-1β and increased pancreatic fibrosis. Finally, the expression of galactosidase-beta 1 (GLB1) was significantly increased in pancreatic β-cells.Conclusion The study findings indicate that senescence, as revealed by an increase in GLB1 expression, is a key factor in the initial stage of diabetes.
Keywords: Diabetes- pancreatic cells, cellular senescence, histomorphology, markers